2021
DOI: 10.1002/rmv.2203
|View full text |Cite
|
Sign up to set email alerts
|

How strong is the evidence that it is possible to get SARS‐CoV‐2 twice? A systematic review

Abstract: Summary With a large number of coronavirus disease 2019 (Covid‐19) patients being discharged from hospital with negative test results for SARS‐CoV‐2, it has been reported that several recovered cases tested positive after discharge (re‐positive, RP). This finding has raised several important questions for this novel coronavirus and Covid‐19 disease. In this review, we have discussed several important questions, including: (1) Can the virus re‐infect recovered individuals? (2) What are the possible c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…We found that the prevalence of reinfection after recovery from COVID-19 was very low and that prior infection with SARS-CoV-2 conferred an 80% protective efficacy against reinfection (assuming baseline prevalence of 5%). The existing reviews [23,[97][98][99][100][101][102][103][104][105][106] have not examined the question of prevalent immunity sufficiently (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the prevalence of reinfection after recovery from COVID-19 was very low and that prior infection with SARS-CoV-2 conferred an 80% protective efficacy against reinfection (assuming baseline prevalence of 5%). The existing reviews [23,[97][98][99][100][101][102][103][104][105][106] have not examined the question of prevalent immunity sufficiently (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…In a letter to the editor published at the time of finalization of this review, the prevalence of reinfection in a period of up to 12 months was 0.3% in Italy (112). Findings from this Italian study (101) also suggested a strong protective efficacy of prior infection with a hazard ratio of 0.06 (95%CI 0.005 – 0.08). In the USA, another study of 9119 individuals (113) with serial tests at least 90 days apart, during December 2019 to November 2020, published at the time of finalization of this review, also showed a low prevalence of reinfection of 0.7% (95%CI 0.5-0.9) (89).…”
Section: Discussionmentioning
confidence: 57%
“…Findings from this Italian study (101) also suggested a strong protective efficacy of prior infection with a hazard ratio of 0.06 (95%CI 0.005 – 0.08). In the USA, another study of 9119 individuals (102) with serial tests at least 90 days apart, during December 2019 to November 2020, published at the time of finalization of this review, also showed a low prevalence of reinfection of 0.7% (95%CI 0.5-0.9) (89). More research is also needed to measure protective efficacy in the long term.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We are reporting a case of reinfection with SARS‐CoV‐2 during a pregnancy in a healthy, immunocompetent woman. The woman had mild symptoms in both episodes, but milder symptoms during the first episode, as reported in most, but not all, previous case reports on reinfection with SARS‐CoV‐2 13 . Unfortunately, the first serology test was not done earlier than 2 months after the first infection.…”
Section: Discussionmentioning
confidence: 74%